The Johns Hopkins manual of gynecology and obstetrics 2026-02-16T15:31:45+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Bienstock, Jessica L. editor; Fox, Harold E. (Harold Edward), 1945-; Hallock, Jennifer L.; Johnson, Clark T.; Wallach, Edward E., 1933- (Wolters Kluwer, 2015)

(untitled)
From the Department of Gynecology and Obstetrics at The Johns Hopkins University School of Medicine comes the Fifth Edition of this outstanding resource. The Johns Hopkins Manual of Gynecology and Obstetrics is your on-the-spot reference for virtually any situation you'll face in obstetrics, high-risk obstetrics, gynecology, reproductive endocrinology, infertility, and gynecologic oncology. It's also highly effective as a review tool for certification or recertification exams.--Publisher's website